Síntese de copolímeros em bloco por reações one-pot com processos RAFT e ROP simultâneos - Freitas, Augusto Gonzaga Oliveira de (2016)
The present work describes a methodology of controlled synthesis of block copolymers by one-pot reactions involving simultaneous RAFT and ROP processes mediated by a bifunctional compound which acts as a chain transfer agent (CTA) for the RAFT process and co-initiator of the ROP process. Reactions involving the RAFT of Styrene (St) and the ROP of ε-Caprolactone (ε-CL) were performed to obtain PS-b-PCL diblock copolymers. The catalysts Sn(Oct)2 and diphenyl phosphate (DPP) were evaluated in the ROP process. Diphenyl phosphate is the most appropriate for this kind of reaction, since Sn(Oct)2 proved to be avid when interacted with CTA, interfering antagonistically in the radical equilibrium of the RAFT process. The reactions were always controlled when DPP was used as a ROP catalyst, wherein copolymers with narrow molar mass distribution were obtained in the end. This methodology was employed in the synthesis of other linear and graft amphiphilic block copolymers, proving to be an excellent alternative for this purpose. Thermoresponsive copolymers based on Poly(oligo(ethylene glycol)methyl ether methacrylate) (POEGMA) and pH responsive based on Poly(acrylic acid) (PAA) were obtained. The physicochemical properties of the copolymers were investigated in solid state as well as in solution, and the results are in total agreement with values reported in the literature.